PROTOTIPE MONITORING SUHU RUANGAN DAN DETEKTOR GAS BOCOR BERBASIS APLIKASI BLYNK - Sastra Utara, Gede; Wirastuti, N.M.A.E.D.; Setiawan, Widyadi (Jurnal SPEKTRUM, 2020)
In everyday life we often use the name LPG gas even as basic needs. However, in its use it can pose a threat because of a large enough LPG gas. The occurrence of gas leaks when there are no people around the leak is very difficult to detect especially lethal substances contained in LPG gas. To reduce fires caused by LPG gas leaks, a monitoring system is needed to monitor if a leak occurs.The prototype method for monitoring room temperature and gas detector leak using the Arduino uno 328 mitrocontroller by connecting ESP8266 for wifi connection. ESP8266 will send data when the MQ2 sensor reads a gas leak, as well as changes in room temperature that is read by the DHT11 sensor by sending the sensor reading data to Arduino ATmega 328 first to be processed into the response data of the device and data that will be displayed on the blynk application.The result of the achievement of this research is that the measurement of leaky gas using the MQ2 sensor can already be displayed using the avo meter by obtaining the voltage results. Real gas leakage measurements in the field can be displayed on mobile phones through the Blynk application media. The leaked gas graph can be displayed in the Blynk application by getting the minimum and maximum results. The ESP8266 module must be located in an area or location that has a Wi-fi network in order to send notifications properly according to the instructions on Arduino ATmega 328.